2020
DOI: 10.1111/tbed.13872
|View full text |Cite
|
Sign up to set email alerts
|

Potential zoonotic sources of SARS‐CoV‐2 infections

Abstract: The severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) causing coronavirus disease‐2019 (COVID‐19) likely has evolutionary origins in other animals than humans based on genetically related viruses existing in rhinolophid bats and pangolins. Similar to other animal coronaviruses, SARS‐CoV‐2 contains a functional furin cleavage site in its spike protein, which may broaden the SARS‐CoV‐2 host range and affect pathogenesis. Whether ongoing zoonotic infections are possible in addition to efficient human‐t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 62 publications
0
94
1
4
Order By: Relevance
“…Reports showed that humans can become a source of infection for minks, which has resulted in a disease outbreak [ 12 , 13 ]. Equally, epidemiologic evidence supported by genomic sequencing corroborated mink-to-human transmission events in farms [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reports showed that humans can become a source of infection for minks, which has resulted in a disease outbreak [ 12 , 13 ]. Equally, epidemiologic evidence supported by genomic sequencing corroborated mink-to-human transmission events in farms [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…While many mutations have been discovered, there is focus on the Y453F mutant in the RBD, as a preliminary report shows that this mutation increases the affinity of the RBD for the human ACE2 receptor ( 37 , 38 ). The mink is now a well-known animal reservoir for SARS-CoV-2, and transmission to humans has been demonstrated ( 39 ). While further investigation is needed to determine whether the mutations in this mink outbreak could epidemiologically worsen the COVID-19 pandemic, the principle remains that mutations in the RBD may yield more transmissible variants.…”
Section: The Case For S2: Benefits Of the Structural Conservation Of mentioning
confidence: 99%
“…It is hypothesized that a virus-tolerant phenotype in bats has facilitated the co-evolution of bat hosts with viral pathogens [ 148 ]. Molecular epidemiological studies of the origins of CoVs have linked SARS-CoV-like CoVs in bats as the reservoirs to SARS-CoV, MERS-CoV, and endemic HCoV-NL63 and HCoV-229E [ 16 , 149 ]. Recent research suggests that bats are the evolutionary reservoir to SARS-CoV-2 [ 105 , 141 , 150 ].…”
Section: Animal Host Diversity Of Sars-cov-2mentioning
confidence: 99%